Needs in moral and political philosophy - Brock, G; Miller, D (Metaphysics Research Lab, Stanford University, 2019)
Much ordinary discourse about political and moral matters invokes the language of needs. In such contexts claims about need are often thought to carry significant weight. By contrast, the role that needs should play in normative reasoning is contested among philosophers. In this article we discuss several core issues concerning needs in contemporary moral and political philosophy. We begin by discussing the normativity of needs and some of the disputes concerning the significance of needs claims.